Structure of the relationship between psychophysiological indicators of players in modern volleyball - R. O. Bondar (Kazimierz Wielki University, 2020)
The paper defines the relationship structure of setter players psychophysiological indicators in modern volleyball using factor analysis. It is found that this structure is composed of five orthogonal factors with total fraction 72,2% of the total variance of the study group. The most important components are the regulatory factor, cognitive, the adaptive response factor, athlete psycho-emotional state factor and neurodynamic factor.